Analisis Efektivitas Biaya Antinyeri Pasien Diabetik Neuropati Di Puskesmas Kaliwungu Kudus Dan RSI Sultan Agung Semarang - Isna Rahmawati (Jurnal Farmasi Indonesia, 2022)
Diabetic neuropathy that affects peripheral nervous system as a complication of Diabetes Mellitus (DM). A total of 1785 DM patients in Indonesia, 63.5% experienced neuropathy. Choosing the right analgetics for diabetic neuropathy patients will improve therapy, so the costs of using the drugs will also be affordable. This study aims to cost effectiveness analysis of analgetics in diabetic neuropathy patients at Kaliwungu Kudus Health Center and Sultan Agung Islamic Hospital in Semarang. This study was hold in September - November 2020. The research method was cohort retrospective and collected data with purposive sampling involving all populations who had complete medical record and include inclusion criteria. The instruments used were data report, medical record and details of the patient's payment. The cost data used was based on a payer perspective from direct medical costs related to drug prices based on perspective of the hospital and e-catalogue or BPJS. Then CEA to determine which therapy was more cost-effective therapy from the use of analgeticss by calculating the ACER (Average Cost Effectiveness Ratio) and ICER (Incremental Cost Effectiveness Ratio). The results show that the cost effectiveness of analgetics at the Kaliwungu Kudus Health Center is diclofenac sodium 50 mg and a combination of 500 mg paracetamol and 200 mg ibuprofen with ICER values of Rp. 2765.02 and Rp.-8,837.94. Meanwhile, at the Sultan Agung Islamic Hospital in Semarang, are single amitriptyline and a combination of amitriptyline and tramadol, with the ICER value on single amitriptyline which is Rp. -7,690.08.